Differences In The Effect Of Baby Massage And Baby Spa On The Growth And Motoric Development Of Infants Aged 3 - 6 Months At Pmb Cakung Kelurahan, Jakarta Timur - Mariatul Qibtiah; Mariyani Mariyani (Lembaga Pengembangan Kinerja Dosen, 2023)
Background : The age of infants and toddlers is the golden age of the period of growth and development of a human being. To stimulate the growth and development of the baby, it is necessary to stimulate the baby. Baby massage and spa are activities to optimize the growth and development of babies. Research objective : to determine the effect of baby massage and baby spa on the growth and motoric development of babies aged 3 to 6 months. Research Methods : This study used a quasi-experimental and pretest and post-test design with a control group. The number of samples of infants aged 3-6 months was 60 babies, 20 babies for the baby massage group, 20 babies for the baby spa group (solus per aqua) and 20 babies who were not treated because their parents refused. The instruments used in this study were baby scales, tape measure and DDST II. Data analysis in this study was the Wilcoxon and Mann Whitney tests. The results of the study: There is an influence of baby massage and baby spa interventions on the growth and motor development of infants aged 3-6 months with p-Value = 0.000 (<0.05). The Mann Whitney test results obtained a p-value of 0.000 (p-value <0.05 at α = 5%), so that it can be concluded that there are differences in the growth and motor development of infants aged 3 to 6 months between the control group and the intervention group (who get baby massage and baby spa). Conclusions and suggestions : It is hoped that baby massage and baby spa can optimize baby growth and development. There is a difference in the effect of giving baby massage and baby spa on the growth and motoric development of infants aged 3-6 months. So that giving actions like this can be routinely carried out to maximize the growth and development of the baby.